International Student Challenges Further Amplified in the Era of a Pandemic: A Tale of a Bangladeshi Graduate Student - Zabin, Rakha (Journal of International Students, 2022)
International students have always been in challenging situations and this pandemic amplified it further. To smoothly transition to the educational platforms and integrate into a new country, especially during and after the Covid-19 pandemic, international students need adequate support from educational institutions and governments. Integration plays a dominant role in adaptation to life in a foreign country and academic success. Based on Tinto's (2011) integration model, this study explores the unique challenges based on the lived experiences of an international doctoral student from a lower-income country, Bangladesh, enrolled in an Ontario university. It focuses on the learning experience of the international doctoral student's integration to become a scholar within this changing time. Self-reflection on the hurdles experienced and the coping strategies during the evolution inform the analysis. Finally, the study concludes by highlighting the role of adequate institutional and government support services by offering valuable recommendations for international students’ integration.